2015
DOI: 10.1016/j.conbuildmat.2015.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour at high temperature of alkali-activated aluminosilicates (geopolymers)

Abstract: g r a p h i c a l a b s t r a c t a b s t r a c tThis study was designed to determine the effect of temperature on the mechanical strength (in both in vivo and post-exposure trials) of two alkaline cements (without OPC): (a) 100% fly ash (FA) and (b) 85% FA + 15% bauxite, the activated alkaline solution used was 85% 10-M NaOH + 15% sodium silicate. A Type I 42.5 R Portland cement was used as a control. Two series of trials were conducted: (i) in vivo trials in which bending and compressive strength, fracture t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 32 publications
8
39
0
1
Order By: Relevance
“…The better mechanical behaviour of HYC at 600 °C might be related to the alkaline (sodium), fly ash and in general high amorphous phase content in the matrix ( Table 2). In earlier studies, pseudo-viscous phases were observed to form in fly ash-based alkaline cement at around 500 °C (34). Vitreous transition at 560 °C (52) and hightemperature softening have also been reported in fly ash alkaline cement (53).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The better mechanical behaviour of HYC at 600 °C might be related to the alkaline (sodium), fly ash and in general high amorphous phase content in the matrix ( Table 2). In earlier studies, pseudo-viscous phases were observed to form in fly ash-based alkaline cement at around 500 °C (34). Vitreous transition at 560 °C (52) and hightemperature softening have also been reported in fly ash alkaline cement (53).…”
Section: Discussionmentioning
confidence: 82%
“…In the DT tests, cracks formed unstably and after extending rapidly under loading, grew spontaneously with no need to raise the load (34). Greater OPC deterioration was nonetheless obviously related to the presence of general cracking in the matrix.…”
Section: Sem Findingsmentioning
confidence: 98%
See 1 more Smart Citation
“…The existing publications on fire resistance and performance of AAM under high temperature conditions are promising. The stability at high temperatures of binders made by the alkaline activation of aluminosilicate precursors is clearly distinct from the behavior observed in Portland cement at high temperatures (Martin et al, 2015). The shrinkage of AAM up to 600 • C temperature occurs due to evaporation of the adsorbed and weakly bound water.…”
Section: Introductionmentioning
confidence: 82%
“…On one hand, high alkali content in activation solution (8 to 12 M NaOH solutions) is necessary to accelerate the activation reactions of precursors and to obtain AAM with high initial strength, but at the same time increased concentration of alkalis could act as fluxes at high temperatures. Therefore, the content of alkalis in the alkali activation solution must be limited to generate thermally stable materials (Martin et al, 2015). It has been reported that the alkali concentration in the activation solution could be reduced event to 2 M (Huiskes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%